Asparagopsis taxiformis: potential and perspective for Vietnam seaweed industry to reduce CH\(_4\) emission in animal husbandry - Pham, Thi Minh Thu; Ngo, Dang Nghia (Vietnam Journal of Marine Science and Technology, 2025)
Climate change has become a major issue for humanity nowadays, requiring comprehensive solutions on a global scale. The primary cause of climate change is the excessive absorption of solar energy due to the emission of greenhouse gases into the atmosphere. Alongside the main agent, CO2, which accounts for two-thirds of global warming, other gases such as methane, nitrous oxide, and fluorinated gases are significant contributors. Methane emissions from livestock farming activities, primarily from cattle, play a crucial role. Although methane emissions are lower than CO2, it has a much greater ability to absorb solar radiation than CO2. In efforts to reduce methane emissions from livestock, scientists have conducted research on defauna of methanogens or inhibit the production of hydrogen, which is necessary for methane synthesis, by altering the composition or adding some ingredients to feed. Among the effective ways to reduce the methane emission, an important discovery is that the red algae Asparagopsis, including two species Asparagopsis amata and Asparagopsis taxiformis, which contain bromine compounds, when being added to feed, have a very strong inhibitory effect on methane production in bovine rumen. One of them, A. taxiformis, is distributed in many coastal provinces of Vietnam. With the high global consumption of cattle feed, the demand for Asparagopsis is substantial. However, due to its complex biological characteristic and life cycle, large-scale cultivation technology for this seaweed still faces many challenges. In this article, we summarize fundamental issues and related challenges in cultivating A. taxiformis. We cover the mechanism of methane production in the bovine rumen and methods to inhibit it, the biological characteristics and life cycles of the algae, nursery and cultivation techniques, as well as the climate conditions and challenges for developing the seaweed industry in Vietnam. Moreover, we also report preliminary results on sample collection and morphology analysis of A. taxiformis in Nha Trang, Khanh Hoa to support its potential, both nationwide and specially in Nha Trang.